1987
DOI: 10.1039/c39870000573
|View full text |Cite
|
Sign up to set email alerts
|

The generation and microwave spectrum of propadienethione, H2CCCS

Abstract: The third member of the cumulenethione series, H2CnS, propadienethione, has been produced by pyrolysis of cyclopenteno-I ,2,3-thiadiazole and detected by microwave spectroscopy which provided rotational parameters for the 32s and 3 4 s isotopomers, the dipole moment [2.064(8) Debye], and an indication that propadienethione is a planar molecule of C2" symmetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
100
0
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 0 publications
1
100
0
2
Order By: Relevance
“…Note that we have done highly accurate simulations in order to eliminate random error, and identify any sources of systematic error. This result is consistent with, but more accurate than, the result obtained from periodically sampled diffusion paths by Zhou et al 8 This result agrees with the most recent boundary-element calculations, 29,30 to the accuracy available with those methods. 24 However, our approach is exact in principle for the class of absorbing surfaces we treat, in the sense that no systematic error is present.…”
Section: ͑42͒supporting
confidence: 82%
See 1 more Smart Citation
“…Note that we have done highly accurate simulations in order to eliminate random error, and identify any sources of systematic error. This result is consistent with, but more accurate than, the result obtained from periodically sampled diffusion paths by Zhou et al 8 This result agrees with the most recent boundary-element calculations, 29,30 to the accuracy available with those methods. 24 However, our approach is exact in principle for the class of absorbing surfaces we treat, in the sense that no systematic error is present.…”
Section: ͑42͒supporting
confidence: 82%
“…Boundary-element estimates of this quantity differ substantially. 27,[29][30][31] Our result for this quantity is C͑unit cube͒ϭ0.660 675Ϯ0.000 01 ͑4.3͒…”
Section: ͑42͒mentioning
confidence: 99%
“…A volume of 4 L of treated water with a NO 3 -concentration of 50 mg/L was obtained after MSDS operation for 90 min. It was found that NO 2 -and H 2 O 2 were produced in the water by the plasma discharge treatment. In addition, the O 3 concentration in the water also increased.…”
Section: Discussionmentioning
confidence: 99%
“…There are several techniques to promote plant growth 1 . In the control of light, effective lights for the photosynthesis of plants are provided efficiently 2,3 . In temperature control, the optimum temperature is maintained for plant growth 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…[1] For example, several groups have reported the reduction of the C=C double bonds of a,b-unsaturated esters with NaBH 4 -NiCl 2 in the synthesis of numerous natural and unnatural bioactive molecules. [2] The NaBH 4 -NiCl 2 system has also been used in the reduction of aliphatic nitro groups or nitroarenes to amines, [3] a-amino acids to 1,2-amino alcohols, [4] 4,5-dihydro-2-oxazole to oxazolidine, [5] and in desulfurization processes.…”
mentioning
confidence: 99%